Enhancing Growth in Tourism SMEs: A Decision-Making Framework Utilizing the Analytic Hierarchy Process - Hermawati, Adya; Sembhodo, Abimanyu Tuwuh; Fatmawati, Endang; Fettry, Sylvia; Wibowo, Teguh Setiawan (Jurnal Aplikasi Manajemen, 2024)
The urgency of revitalizing Indonesia's tourism sector post-pandemic is critical as the industry continues to face significant challenges in recovery. This research objective is to identify the key variables and specific regions that should be prioritized to enhance national tourism statistics. Employing a cross-sectional survey methodology, data were collected from 1,320 employees across 440 tourism SMEs in 11 regions of East Java, alongside insights from 33 policymakers. The research utilized the Analytic Hierarchy Process (AHP) to systematically compare and prioritize variables, integrating quantitative and qualitative data. The findings reveal that market orientation is the most crucial factor for the success of tourism SMEs in East Java, with Banyuwangi identified as the region with the highest potential for maximizing tourism performance. The novelty of this research lies in the application of AHP as a methodological framework, which facilitates a structured decision-making process informed by the expertise of diverse stakeholders. The implications of this study suggest that by adopting a market-oriented approach and implementing tailored strategies for specific regions, tourism SMEs can enhance their competitive advantage and significantly contribute to the overall growth of the tourism sector. Prioritizing Banyuwangi could unlock substantial economic benefits, reinforcing the region's tourism potential and driving broader economic prosperity.